1999
DOI: 10.1097/00007890-199903150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination in Liver Transplant Recipients

Abstract: Our results show that the vaccine is safe and effective and should be recommended to TXL-R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 6 publications
3
39
0
Order By: Relevance
“…47,67 Adult liver transplant recipients have also been reported to be adequately protected by the vaccine. In the study of Burbach et al, 65 protective postimmunization titers at 21 days for the 3 antigens contained in the vaccine (A/Bayern/07/95, A/Wuhan/359/95, and B/Bejing/ 184/93) were 92%, 92%, and 95% in liver transplant recipients compared with 97%, 100%, and 100% in healthy controls, respectively. 65 Seroconversion was defined as a postvaccination titer of 1:40 or greater or a 4-fold increase of the prevaccination titer.…”
Section: Vaccinationmentioning
confidence: 97%
See 3 more Smart Citations
“…47,67 Adult liver transplant recipients have also been reported to be adequately protected by the vaccine. In the study of Burbach et al, 65 protective postimmunization titers at 21 days for the 3 antigens contained in the vaccine (A/Bayern/07/95, A/Wuhan/359/95, and B/Bejing/ 184/93) were 92%, 92%, and 95% in liver transplant recipients compared with 97%, 100%, and 100% in healthy controls, respectively. 65 Seroconversion was defined as a postvaccination titer of 1:40 or greater or a 4-fold increase of the prevaccination titer.…”
Section: Vaccinationmentioning
confidence: 97%
“…In the study of Burbach et al, 65 protective postimmunization titers at 21 days for the 3 antigens contained in the vaccine (A/Bayern/07/95, A/Wuhan/359/95, and B/Bejing/ 184/93) were 92%, 92%, and 95% in liver transplant recipients compared with 97%, 100%, and 100% in healthy controls, respectively. 65 Seroconversion was defined as a postvaccination titer of 1:40 or greater or a 4-fold increase of the prevaccination titer. In a recent study, Soesman et al 66 found a seroconversion rate of 68% in liver transplant recipients after 1 dose of the vaccine, which increased to 80% after a second dose.…”
Section: Vaccinationmentioning
confidence: 97%
See 2 more Smart Citations
“…18 Influenza vaccination has reduced the morbidity and perhaps the mortality from influenza virus infection in liver transplant patients with protective post-immunization antibodies. [19][20][21] Its safety and efficacy in liver transplant and other solid-organ recipients have been proven in several studies. 19,[21][22][23][24][25] Although our case suggests that GBS may occur in liver transplant recipients after influenza vaccination, the very low incidence of vaccine-associated GBS, the significantly increased complications from influenza virus infection in solid organ recipients, and the rise of influenza drug resistance make influenza vaccination the first-line strategy for influenza virus infection prevention in solid-organ recipients.…”
Section: Discussionmentioning
confidence: 99%